Niewirusowy transfer genów do komórek skóry – wybrane metody = Non-viral gene transfer into skin cells – selected methods - Wędrowska, Ewelina; Gawroński, Maciej; Wandtke, Tomasz; Goede, Arkadiusz; Wędrowski, Mateusz; Piskorska, Elżbieta (Journal of Education, Health and Sport, 2016)
Wędrowska Ewelina, Gawroński Maciej, Wandtke Tomasz, Goede Arkadiusz, Wędrowski Mateusz, Piskorska Elżbieta. Niewirusowy transfer genów do komórek skóry – wybrane metody = Non-viral gene transfer into skin cells – selected methods. Journal of Education, Health and Sport. 2016;6(1):157-170. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.45147 http://ojs.ukw.edu.pl/index.php/johs/article/view/45147 https://pbn.nauka.gov.pl/works/704486 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.12.2015. Revised 12.01.2016. Accepted: 25.01.2016. Niewirusowy transfer genów do komórek skóry – wybrane metody Non-viral gene transfer into skin cells – selected methods Ewelina Wędrowska1, Maciej Gawroński1, Tomasz Wandtke1, Arkadiusz Goede1, Mateusz Wędrowski2, Elżbieta Piskorska3 1Zakład Genoterapii, Uniwersytet Mikołaja Kopernika w Toruniu, Collegium Medicum im. L. Rydygiera w Bydgoszczy 2Zakład Pozytonowej Tomografii Emisyjnej i Diagnostyki Molekularnej, Uniwersytet Mikołaja Kopernika w Toruniu, Collegium Medicum im. L. Rydygiera w Bydgoszczy 3Katedra Patobiochemii i Chemii Klinicznej, Uniwersytet Mikołaja Kopernika w Toruniu, Collegium Medicum im. L. Rydygiera w Bydgoszczy 1Department of Gene Therapy, Faculty of Medicine, Nicolaus Copernicus University Collegium Medicum, Bydgoszcz, Poland 2Department of Positron Emission Tomography and Molecular Diagnostics, Nicolaus Copernicus University Collegium Medicum, Bydgoszcz, Poland 3Department of Pathobiochemistry and Clinical Chemistry, Nicolaus Copernicus University Collegium Medicum, Bydgoszcz, Poland Streszczenie Wprowadzenie: Skóra jako największy i najłatwiej dostępny narząd stanowi atrakcyjny cel dla terapii genowej, która od wielu lat budzi ogromne nadzieje środowiska naukowego. Jednakże, próby terapii przeprowadzone z wykorzystaniem wektorów wirusowych wykazały szereg wad i ograniczeń m.in. obserwowano indukcję odpowiedzi immunologicznej, losową integrację transgenu z genomem gospodarza i/lub niską wydajność jego ekspresji. Dlatego, wciąż poszukuje się alternatywnych, skuteczniejszych i jednocześnie bezpieczniejszych metod transferu genów. Atrakcyjnej alternatywy upatruje się w metodach niewirusowych. Cel pracy: Przedstawienie wybranych metod niewirusowego transferu genów wykorzystywanych w terapii genowej chorób skóry. Skrócony opis stanu wiedzy: Terapia genowa chorób skóry obejmuje wykorzystanie wektorów plazmidowych jako nośnika genów terapeutycznych, a także metod ich dostarczania do komórek takich jak: elektroporacja, mikroiniekcja, sonikacja, wykorzystanie nośników lipidowych i polimerów kationowych. Podsumowanie: Niewirusowe metody transferu genów oferują pewne zalety włączając niską toksyczność, brak infekcyjności oraz łatwość i niskie koszty produkcji w porównaniu z technikami wirusowymi. Niewirusowe metody wydają się być obiecującym narzędziem terapii genowej chorób skóry w szczególności nowotworów tego narządu. Słowa kluczowe: plazmid, transfer genów, skóra, wirus, terapia genowa. Summary Introduction: Skin, the largest and most accessible organ of the human body is considered as an ideal gene therapy target. However, various types of viral vectors used in classical gene therapy have a number of disadvantages, such as possibility of immune response induction, random integration of inserts into the host genome or low expression efficiency. Therefore, there is an urgent need for alternative, non-viral methods of gene transfer. Aim of the study: To present methods for non-viral gene transfer used in gene therapy of skin diseases. Short description of knowledge state: Gene therapy for skin diseases include the usage of plasmid vectors as a carrier for therapeutic genes and different methods for their delivery into cells such as: electroporation, microinjection, sonication, lipid carriers and cationic polymers. Summary: Non-viral gene transfer methods offer some advantages including lower toxicity, non-infectious properties, ease of production and low costs as compared to viral techniques. Non-viral approaches are the promising tool in gene therapy of skin diseases, in particular in skin cancer ceases. Key words: plasmids, gene transfer, skin, viruses, gene therapy.